ChemInform Abstract: Cu‐Catalyzed Click Reaction in Carbohydrate Chemistry. Issue 17 (April 2016) - Tiwari, Vinod K.; Mishra, Bhuwan B.; Mishra, Kunj B.; Mishra, Nidhi; Singh, Anoop S.; Chen, Xi
Abstract: Review: 747 refs.